(untitled) (Bangladesh Journal of Botany, 2024)
In the present study, 12 introduced Iodent hard kernel maize inbred lines were used as test materials, and four backbone maize inbred lines (JM005, JM006, JF003 and JF004) selected by the present team were tested. NC II genetic mating design was used for combining ability determination and genetic analysis. Results showed that the yield general combining ability effect of test varieties JM005 and JM006 were excellent. Among the Iodent hard maize inbred lines tested, I215, I308, I130, I102, I120, I209 and I401 showed excellent yield GCA effect. Hybrid combination I215 × JM005, I130×JM005, I598×JM005, I102×JM006, I120×JM005, I215×JF004 had a strong super parent advantage in yield, which can be further tested. Bangladesh J. Bot. 53(3): 643-651, 2024 (September) Special